2009
DOI: 10.1080/07418820802593345
|View full text |Cite
|
Sign up to set email alerts
|

Using Propensity Score Matching to Understand the Relationship between Gang Membership and Violent Victimization: A Research Note

Abstract: Due to methodological limitations, such as unmatched gang samples and a lack of longitudinal investigations, it remains unresolved whether joining a gang leads to future violent victimization or both share a set of common causes. Guided by selection, facilitation, and enhancement perspectives, the current study applied Propensity Score Matching on data from the Gang Resistance Education and Training longitudinal study to investigate the nature of the gang-violent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
91
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(95 citation statements)
references
References 47 publications
4
91
0
Order By: Relevance
“…Similarly, Decker et al (2014) reported that self-nomination as a current or former gang member is a strong predictor of 'embeddedness' in gangs, as measured by other survey items. In general, these findings support Thornberry et al's (2003: 22) claim that '[US] Adolescents appear to know what gangs are and whether they are a member of a gang' (Esbensen et al 2001;Gibson et al 2009). …”
Section: Introductionsupporting
confidence: 80%
“…Similarly, Decker et al (2014) reported that self-nomination as a current or former gang member is a strong predictor of 'embeddedness' in gangs, as measured by other survey items. In general, these findings support Thornberry et al's (2003: 22) claim that '[US] Adolescents appear to know what gangs are and whether they are a member of a gang' (Esbensen et al 2001;Gibson et al 2009). …”
Section: Introductionsupporting
confidence: 80%
“…Part of what makes this line of inquiry-the direct and indirect pathways-criminologically compelling are the mixed findings in the literature, which is perhaps best exemplified by contradictory results produced by Gibson et al (2009) and Ozer and Engel (2011) using the same source of data (the first evaluation of the Gang Resistance Education and Training program) and similar counterfactual methodology. Gibson et al (2009: 639) concluded ''In sum, our results showed support for the selection perspective because the relationship between joining a gang and becoming violently victimized was explained by pre-existing differences that perhaps lead gang members to join a gang in the first place.''…”
Section: Advancing Knowledge On the Gang Membership-victimization Linkmentioning
confidence: 88%
“…In a recent review of this literature, Fox (2013Fox ( : 1035 argued that the ''analysis of the gang-victimization link should include examinations of longitudinal data and controls for delinquency/ crime.'' Longitudinal studies, alternatively, have focused on the contemporaneous and prospective direct effects of gang membership on victimization (Barnes et al 2012;DeLisi et al 2009;Gibson et al 2009;Ousey et al 2011;Ozer and Engel 2011;Spano et al 2008;Sweeten et al 2013), leaving the specific mechanisms that bring about this relationship unresolved, which Fox (2013Fox ( : 1016 identified as a key direction in her commentary on the literature.…”
Section: Advancing Knowledge On the Gang Membership-victimization Linkmentioning
confidence: 96%
See 2 more Smart Citations